Characterization of the Gelatinase System of the Laminar Human Optic Nerve, and Surrounding Annulus of Bruch's Membrane, Choroid, and Sclera - Hussain, Ali A. (Invest Ophthalmol Vis Sci, 2014)
PURPOSE. We determined the presence and levels of gelatinase matrix metalloproteinases (MMPs) in the optic nerve and surrounding rim region of the human fundus. METHODS. Samples of optic nerve, rim region, and Bruch's membrane-choroid from macular and peripheral regions were isolated from 9 pairs of human donor eyes. The MMPs were extracted and separated by gelatin zymography. Individual gelatinase species were identified by their respective molecular weights and levels quantified by standard densitometric techniques. Ratios of active/latent MMPs were calculated as representative indicators of the degree of proteolytic activity at each of the locations examined. RESULTS. All of the gelatinase species normally found in Bruch's membrane also were present in the optic nerve region. The presence of the high molecular weight MMP species (HMW1 and HMW2) was indicative of the age-related accumulation of polymerized MMPs 2 and 9. Level of activated MMPs was considerably raised in comparison with their latent forms at the optic nerve and surrounding region indicative of greater ongoing turnover of the matrix (P < 0.005). CONCLUSIONS. The components of the gelatinase pathway mediating matrix turnover in Bruch's membrane also were present in the optic nerve region. The presence of high levels of active MMPs 2 and 9 in comparison with the latent forms in the optic nerve and rim area is indicative of a high rate of matrix remodeling in these regions. Enhanced matrix turnover within the optic nerve region may represent an important mechanism for maintaining the plasticity of the lamina cribrosa.